Use of neural networks for the estimation of nickel content in lateritic bark with radioactive methods of wells - Guerra, Marcial; Ruíz, Jorge; Ebecken, Nelson; Landau, Luiz; Silva, Josias (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
The aim of the present work is a preliminary set of groups that make up the Crust Lateritico Niqueliferas Cobaltiferas of Punta Gorda Reservoir in Cuba by neural networks applied to a sef of radioactive well logs according to a predetermined geolical classification . It also undertakes assesment of nickel content in each of the defined groups also implementing neural networks.